Morphological and biochemical characterization of Passiflora quadrangularis L. - A source of vegetable from East Siang district, Arunachal Pradesh, India - Kripa Shankar; Singh S R (Journal of Horticultural Sciences, 2022)
Present research investigation was aimed at morphological and biochemical assessment of Passiflora quadrangularis L. commonly known as giant granadilla and locally called as vegetable squash grown as vegetable crop by the Adi tribe of Arunachal Pradesh. Seven genotypes collected during survey were characterized for different morphological and biochemical traits. Results showed that average fruit weight was 432.57g/fruit, with juice content 100.11 mL/fruit, vitamin C content 25.79 mg, vitamin A content 1.65 mg, Mean total flavonoids content was 16.75 mg/100 g of fruit juice, total soluble solids 12.040 Brix, antioxidant activity (DPPH) 6.07 %, titratable acidity 1.69 %, total carbohydrates 9.95 %, phenol content 338.38 mg/100 g of leaf was noted among the genotypes tested. The mean anthocyanin content in leaf was 1.20 mg/100 g, tendril 0.90 mg/100 g and petiole 1.69 mg/ 100 g among the genotypes. Seed protein profiling of Passiflora quadrangularis L. with SDS- PAGE showed diverse molecular weights ranging from 11 KD to 163.53 KD. However, monomorphic banding pattern among the protein profiling of giant granadilla was recorded among the selected genotypes. The results of the study show that the collected genotypes are belonged to Passiflora quadrangularis L. and are good source of nutritive value which can be used as source of vegetable.